2002
DOI: 10.1002/jrs.824
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman study of iridium silicides

Abstract: The micro-Raman spectra of three iridium silicides, IrSi, IrSi 1.75 and IrSi 3 , were obtained. The silicides were prepared by rapid thermal annealing of iridium films deposited on Si substrates. The three phases were identified by Rutherford backscattering spectrometry. The main bands observed in the micro-Raman spectra are described in order to provide a simple characterization method for these silicides with high spatial resolution. The three silicides present phonon bands around 165 and 200 cm −1 . Some ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…For this annealed film, except for those of the silicon substrate, no other peaks were observed in the XRD pattern. A similar feature of three well-defined peaks in Raman spectrum has been reported for Ir silicide, IrSi 1.75 [6] ; therefore, we may attribute those three well-defined peaks to manganese silicide, and it indicates that Mn silicide is formed in the film during annealing at 500 • C. After annealing at a higher temperature of 600 • C, the two broad humps corresponding to amorphous Si disappeared, while the peaks corresponding to crystalline silicon and Mn silicide became more intense, indicating further crystallization of Si and Mn silicide in the film annealed at 600 • C. For this annealed film, several weak peaks corresponding to tetragonal Mn silicide, MnSi 1.73 , were observed in the XRD pattern, [3,11] which confirms our conclusion that the set of three well-defined Raman peaks located at 276, 301, and 318 cm −1 originates from Mn silicide, MnSi 1.73 . Figure 2 shows the Raman spectra of as-grown and annealed MnSi x thin films with a Mn concentration of 30%.…”
Section: Methodssupporting
confidence: 52%
“…For this annealed film, except for those of the silicon substrate, no other peaks were observed in the XRD pattern. A similar feature of three well-defined peaks in Raman spectrum has been reported for Ir silicide, IrSi 1.75 [6] ; therefore, we may attribute those three well-defined peaks to manganese silicide, and it indicates that Mn silicide is formed in the film during annealing at 500 • C. After annealing at a higher temperature of 600 • C, the two broad humps corresponding to amorphous Si disappeared, while the peaks corresponding to crystalline silicon and Mn silicide became more intense, indicating further crystallization of Si and Mn silicide in the film annealed at 600 • C. For this annealed film, several weak peaks corresponding to tetragonal Mn silicide, MnSi 1.73 , were observed in the XRD pattern, [3,11] which confirms our conclusion that the set of three well-defined Raman peaks located at 276, 301, and 318 cm −1 originates from Mn silicide, MnSi 1.73 . Figure 2 shows the Raman spectra of as-grown and annealed MnSi x thin films with a Mn concentration of 30%.…”
Section: Methodssupporting
confidence: 52%
“…However, the relative intensity of this feature varies with the employed excitation wavelength as well as with the sample region where the spectrum was acquired, because of different surface integrity. Almendra et al [29] investigated iridium silicides and reported region dependent Raman intensities because of local inhomogeneities of their iridium layers on silicon. Owing to a low Raman scattering efficiency, they also applied long integration times to gain a reasonable signal-to-noise ratio.…”
Section: Raman Measurementsmentioning
confidence: 99%
“…Since the late 1970s, iridium silicides have become attractive for applications in electronic industry [1][2][3][4], and much research has been dedicated to thin film deposition, nucleation and growth of Ir-Si intermetallic phases formed and their stabilities have contributed to optimization of electronic devices [5,6]. Some of Ir-Si intermetallic compounds, such as IrSi, Ir 3 Si 5 [7] and IrSi 3 [4,7,8] are of interest for microelectronic or thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%